MODIFIKASI ALGORITMA GENETIKA UNTUK PENYELESAIAN PERMASALAHAN PENJADWALAN PELAJARAN SEKOLAH (Studi Kasus: SMPN 1 Telaga Gorontalo) - , RAHMAN ERAMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Modified Genetic Algorithm in this study was based on the findings of previous researchers about the weakness of Genetic Algorithms. crossover as one of the most important stages in the Genetic Algorithms considered not guarantee a better solution by several researchers. Based on the findings by previous researchers, this research will try to modify the genetic algorithm by eliminating crossover2 which is the core problem of several researchers. Elimination crossover is expected to create a more effective algorithm as an alternative to the settlement issue in particular scheduling school. This study is intended to modify the genetic algorithm into an algorithm that is more effective as an alternative to solve the problems of school scheduling. So expect the creation of this alternative algorithm could be an additional resource for researchers to solve other scheduling problems. Modified algorithm that eliminates the crossover phase of the genetic algorithm is able to provide 2,30% better performance than standard genetic algorithm in solving scheduling problems school.